2017
DOI: 10.1111/crj.12693
|View full text |Cite
|
Sign up to set email alerts
|

The value of macrophage inhibitory cytokine‐1 level in differentiating benign from malignant solitary pulmonary nodules

Abstract: In conclusion, measurement of serum MIC-1 levels could be considered as a diagnostic biomarker for malignant SPN patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…10 At the same time, serum CEA is widely used for progression monitoring of lung cancer. 11 , 12 , 13 Moreover, several research studies 14 , 15 have reported that serum CEA had a high specificity in detecting lung cancer. While looking for new preferable diagnostic biomarkers, traditional biomarkers in the clinic should be reasonably applied to support the diagnosis of lung cancer.…”
Section: Introductionmentioning
confidence: 99%
“…10 At the same time, serum CEA is widely used for progression monitoring of lung cancer. 11 , 12 , 13 Moreover, several research studies 14 , 15 have reported that serum CEA had a high specificity in detecting lung cancer. While looking for new preferable diagnostic biomarkers, traditional biomarkers in the clinic should be reasonably applied to support the diagnosis of lung cancer.…”
Section: Introductionmentioning
confidence: 99%